Impacto da implantação de segmentos de anel corneanos intra-estromais na qualidade de vida de doentes com queratocone - Anita Antunes Sousa (2018)
Objective: To evaluate the influence of the implantation of intrastromal corneal ring segments (ICRS) on the quality of life of patients with keratoconus, through the National Eye Institute Visual Function Questionnaire-25 (NEI VFQ-25). Material and Methods: Descriptive retrospective study of 18 patients diagnosed with keratoconus, who underwent ICRS implantation between 2011 and 2017. The NEI VFQ-25 was administered, adjusted to the retrospective design of the study and to the portuguese language. The results were evaluated together with pre and postoperative data of best corrected visual acuity (BCVA), maximum curvature of the anterior surface of the cornea (Kmáx), keratometric astigmatism (KA) and root mean square of coma aberration (RMS Coma). Results: Statistically significant improvements were observed in BCVA (p=0.001), from a preoperative median of 0.40 to 0.65, and in the composite score of the NEI VFQ-25 (p=0.001), from 70.21 to 80.51 postoperatively. Additionally, there were statistically significant decreases in Kmáx (p=0.012), from a median of 59.20 to 53.90 diopters, and in RMS Coma (p=0.001), from 2.63 μm to 1.81 μm. The median decrease in KA, from -3.25 to -1.50 diopters, was not statistically significant (p=0.896). Conclusions: The implantation of ICRS in keratoconus significantly improves clinical and topographic measures of vision, as well as patients' quality of life.